The Implementation of Knowledge Management System (KMS) Evaluation Model in Improving Employee Performance - Wahyu Budianto, Wahyu Sardjono (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Employee performance plays a significant role in running a company, and it is important to make every effort to improve this virtue. Therefore, this study aims to assess the KMS evaluation model applied at PLN (State Electricity Company) and determine factors and indicators that improve employee performance. This is a survey study that obtained data through summative evaluation using a questionnaire. Furthermore, the collected data were quantitatively analyzed using descriptive and inferential statistics. The results showed that, (1) the People variable has a positive and significant effect on employee performance, which is evidenced by the T-count value of 3.207 and a significance of 0.0022. (2) Process variables have a positive and significant effect on performance, which is evidenced by the T-count value of 4.263 and a significance of 0.000. (3) Technology variables have a positive and significant effect on performance, which is evidenced by the T-count value of 4.506 and a significance of 0.000. (4) The indicators that improve performance at PT PLN (Persero) include the people variable, which consists of employee roles, communication, training, rewards for sharing knowledge, as well as aBility to access KMS. Furthermore, process variables consist of knowledge creation, storage, retention, sharing, utilization, and work accuracy. In addition, technology variables consist of KM Feature and content quality, as well as molarity barriers..